2012
DOI: 10.3126/hn.v11i1.7208
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Drought Adaptive Traits in Nepalese Wheat (Triticum aestivum L.) Germplasm

Abstract: Wheat (Triticum aestivum L.) is one of the major cereal crops vital for global food supply. Most of the wheat crop in developing world including that of Nepal is either grown with limited irrigation or under rainfed conditions and thus face moisture stress at one or more growth stages limiting grain yield. An experiment was carried out at the Institute of Agriculture and Animal Science, Rampur, Nepal, to evaluate the genetic variability of selected drought adaptive traits in Nepalese wheat germplasm. The wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…60 different genotypes including landraces, advanced lines of NWRP, drought check international cultivars, advanced commercial cultivars derived from CIMMYT were experimented in a greenhouse which showed that NPGR 7504 landrace showed drought adaptive traits including high water use efficiency (WUE) and among the Nepalese cultivars Gautam showed the superior drought adaptive traits (Pokhrel et al, 2013). Vijay cultivar of Nepal has been characterized as drought sensitive while Gautam cultivar has been found to show various positive drought related traits in an experiment conducted within a greenhouse comprising of local landraces, advanced commercial CIMMYT derived cultivars and three international check cultivars (Pokharel and Pandey, 2012).…”
Section: Drought Stress Varietal Trails and Breeding In Nepalmentioning
confidence: 99%
“…60 different genotypes including landraces, advanced lines of NWRP, drought check international cultivars, advanced commercial cultivars derived from CIMMYT were experimented in a greenhouse which showed that NPGR 7504 landrace showed drought adaptive traits including high water use efficiency (WUE) and among the Nepalese cultivars Gautam showed the superior drought adaptive traits (Pokhrel et al, 2013). Vijay cultivar of Nepal has been characterized as drought sensitive while Gautam cultivar has been found to show various positive drought related traits in an experiment conducted within a greenhouse comprising of local landraces, advanced commercial CIMMYT derived cultivars and three international check cultivars (Pokharel and Pandey, 2012).…”
Section: Drought Stress Varietal Trails and Breeding In Nepalmentioning
confidence: 99%